2021
DOI: 10.1021/acs.macromol.1c01521
|View full text |Cite
|
Sign up to set email alerts
|

Homopolymer-Assisted Fusions of Polymer Brushes and Block Copolymer Vesicles

Abstract: The applications of materials are closely associated with surface structures and properties. Surface coassembly of block copolymers (BCPs) and polymer brushes is an effective method to fabricate surface structures with tunable properties. The surface coassembly approach not only provides a method for the fabrication of surface structures but also provides a method for the synthesis of hybrid materials with hierarchical nanostructures. In this research, polystyrene (PS)-assisted fusions of PS brushes on silica … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…The vesicular coassemblies develop pores and curled walls after 12 h of incubation (Figure S9), resulting in compound vesicular coassemblies with an average hydrodynamic diameter of 1.13 μm (Figure S7b). Previous reports of compound vesicles mostly associated with high-concentration fusion of small vesicles, 38 but this compound vesicular coassembly is formed by wall-curling of a single vesicle, similar to block copolymers with a high packing parameter self-assembling directly. 39 After 18 h of incubation, the walls of compound vesicular coassemblies curl even further, resulting in flower-like coassemblies composed of tubular subunits (Figure 2e,f).…”
Section: ■ Results and Discussionmentioning
confidence: 95%
“…The vesicular coassemblies develop pores and curled walls after 12 h of incubation (Figure S9), resulting in compound vesicular coassemblies with an average hydrodynamic diameter of 1.13 μm (Figure S7b). Previous reports of compound vesicles mostly associated with high-concentration fusion of small vesicles, 38 but this compound vesicular coassembly is formed by wall-curling of a single vesicle, similar to block copolymers with a high packing parameter self-assembling directly. 39 After 18 h of incubation, the walls of compound vesicular coassemblies curl even further, resulting in flower-like coassemblies composed of tubular subunits (Figure 2e,f).…”
Section: ■ Results and Discussionmentioning
confidence: 95%
“…Liu and coworkers found that hybrid compound structures composed of silica particles and the fused vesicles could be fabricated by fusion of PS brushes and PEG-b-PS BCP vesicles in the presence of ''free'' PS chains. 196 In the surface co-assembly, the concentrations of BCPs and PS homopolymers are two key factors in the fusion process. To reduce the surface energy and the unfavorable interaction between the solvent and PS, PS brushes on silica particles were fused with BCP vesicles into large hybrid structures (Fig.…”
Section: Surface Nanostructures Fabricated By Co-assembly Of Polymer ...mentioning
confidence: 99%
“…have been widely used to control the shape, size, and microstructure of the assemblies. In addition, post self-assembly methods such as stimuli-responsive shape transformation, 27,28 hierarchical self-assembly, 29,30 and particle fusion [31][32][33] also allow the controlling over the microstructure of soft nanomaterials.…”
Section: Introductionmentioning
confidence: 99%